(untitled) (Editora Impacto Científico, 2025)
Access to high-cost medications through the Unified Health System (SUS) is a right guaranteed by the Federal Constitution, but its implementation faces several challenges, especially for patients with Chronic Obstructive Pulmonary Disease (COPD) in socially vulnerable situations. These patients often require continuous and complex treatments, which are costly, making access a bureaucratic and unequal process. This chapter analyzes the barriers faced by COPD patients and their families, including financial difficulties, information gaps, regional inequality in the distribution of medicines, and structural limitations of the health system. In addition, it discusses the role of public policies, such as the National List of Essential Medicines (RENAME) and complementary programs, which seek to expand access but still have significant gaps. The literature review shows that adequate adherence to treatment depends not only on the availability of drugs, but also on social support and adequate guidance for patients. Strategies to minimize barriers include simplifying administrative processes, continuous monitoring of patients by multidisciplinary teams, and implementing policies that prioritize equitable access to high-cost essential drugs. It can be concluded that strengthening the SUS and expanding support programs are essential to reducing inequalities in access to COPD treatment, ensuring quality of life and adequate disease control for the most vulnerable groups.